(untitled) (IITM Journal of Business Studies, 2025)
This study investigates the interconnectedness of India’s commodity exports with thirteen major global economies from 2000 to 2023, employing the quantile-quantile connectedness approach. The analysis, illustrated through an extensive network graph, highlights significant variations and dependencies across three economic indicators, particularly in extreme distribution scenarios across various export categories. Our findings reveal convoluted non linear and multiscale interdependencies that elucidate global economic behavior, especially in India’s bilateral trade relationships. Economic Policy Uncertainty (EPU), Consumer Price Index (CPI), and Producer Price Index (PPI) of destination countries have a decisive role in the export network, alongside key export categories such as Petroleum, Agriculture, Ores, and Manufacturing, underscoring India’s pivotal role within the global commodity export network. Furthermore, Principal Component Analysis (PCA) is utilized to consolidate economic variable outcomes into a singular, interpretable metric for each commodity category. These results underscore the significance of extreme economic conditions and tail dependencies in shaping policy, with critical implications for international trade and economic strategy. This study’s methodological and sector-specific insights offer valuable guidance to policymakers and economists in understanding global economic interdependence and crafting more resilient trade and economic policies.